Politics of sexuality : identity, gender, citizenship - Carver, Terrell; Mottier, Véronique (Routledge/ECPR studies in European political science, 1998)
This volume reflects a variety of views of the nature of sexuality and politics, balancing theoretical chapters with a wide range of case studies including sexuality in the British armed forces, the sexual policies of the Catholic Church.